Agar concentration interferes with the biometry, photosynthetic pigment content, and anatomy of Selenicereus undatus in vitro - Evens Clairvil; Bruno Henrique Feitosa; Marcelo de Almeida Guimarães; Filipe Almendagna Rodrigues; Joyce Dória; Gabrielen de Maria Gomes Dias; Evaristo Mauro de Castro; Moacir Pasqual (Ciência e Agrotecnologia)
ABSTRACT The micropropagation of dragon fruit (Selenicereus undatus) is an alternative method to produce vigorous plants with high phytosanitary quality. However, depending on the consistency of the growing medium (liquid, semi-solid, and solid), plants can develop physiological and anatomical disorders, impairing their growth and reducing their viability ex vitro. The aim of this study was to evaluate the biometric characteristics, photosynthetic pigments, and anatomical sections of S. undatus plants grown in five concentrations of agar (0.0, 3.5, 7.0, 10.5, and 14.0 g L-1) in MS medium. Biometric characteristics (number of roots, length of the aerial part, and fresh and dry masses of the roots and aerial part of the plants), photosynthetic pigments (chlorophyll a, b, total and carotenoid contents), and anatomy [number of vascular bundles, cross-sectional area (mm2), and length of reserve parenchyma (μm)] were evaluated. Biometric, photosynthetic pigment, and anatomical characteristics differed between S. undatus plants for the different concentrations of agar. Plants grown in agar-free medium showed increased length, aerial and root biomass, indicating enhanced growth. In contrast, plants grown on media containing 10.5 g L-¹ and 14.0 g L-¹ agar exhibited higher levels of chlorophyll a, chlorophyll b, and total chlorophyll. Additionally, carotenoid levels were higher in plants grown on agar, regardless of concentration. Plants grown without agar showed higher vascular bundle count, cross-sectional area, and reserve parenchyma length than those with agar. In this way, S. undatus plants can be micropropagated efficiently in an agar-free medium.